TINGKAT KEPATUHAN PENGGUNAAN OBAT ANTIHIPERTENSI DI PUSKESMAS BANTUL II YOGYAKARTA - Tri Lestari (JURNAL ILMU KESEHATAN BHAKTI SETYA MEDIKA, 2021)
Hypertension is one of the main risk factors for cardiovascular disease and contributes to the highest mortality in the world, including in Indonesia. The success of therapy is not only influenced by the quality of health services and attitude, but also influenced by the level of patient compliance in taking antihypertensive drugs and carring out routine controls to check their condition and blood pressure. The study aims to determine the level of compliance of patients taking antihypertensive drugs and control back according to the recommendation/schedule at the Bantul II Health Center. The research is an observational descriptive study conducted in June-July 2019. The number of samples is 65 respondents and the sampling technique is accidental sampling. Measuring the level of adherence to taking medication using the MMAS-8 questionnaire and measuring the level of compliance with returning to the doctor using an additional questionnaire. Data were analyzed descriptively qualitatively and presented in tabulated form. The results showed that the level of adherence to the use of antihypertensive drugs at the Bantul II Health Center was 36,8% in the low category, 12,3% in the medium category and 50,7% in the high category. The level of compliance for control back to the doctor was 4,6% in the non adherent category, 24,6% in the less compliant category and 70,8% in the obedient category.